Relationship of Carboxyhemoglobin (CoHb) And Hemoglobin (Hb) Levels In Active Smokers In Gresik Regency - Roudhotin Nur Azizah; Ayu Puspitasari; Indah Lestari; Ismath Mohammad (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Smoking habits negatively affect the body to cause death. This is because cigarettes contain many harmful chemicals. The purpose of this study was to analyze the relationship between carboxyhemoglobin levels and hemoglobin levels in active smokers in Gresik Regency using the Conway dish method which was read with a spectrophotometer. This research was conducted in March-June 2023 at the Toxicology and Hematology Laboratory, Department of Technology, Medical Laboratory, Poltekkes, Ministry of Health, Surabaya using an analytical observational research type. The test material used is whole blood, with research variables of COHb and Hb levels. The results of the analysis showed an average COHB and Hb of 0.89% and 14.6 g / dl with a significance value of 0.304 using the Spearman correlation test. With the limitations of the variables studied, it can be concluded that there is no relationship between COHb and Hemoglobin in active smokers in Gresik Regency.